2018
DOI: 10.1007/s10157-018-1631-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum Na–Cl level and renal function decline in chronic kidney disease: results from the chronic kidney disease Japan cohort (CKD-JAC) study

Abstract: Our investigation suggests that Na-Cl is an independent predictor of CKD progression, especially among patients with CKD stage G4 and those with anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
2
15
0
1
Order By: Relevance
“…Multiple regression analysis revealed that the progression of G category was a significant risk factor for anemia; other risk factors included female sex, low serum albumin level, narrower difference between sodium and chloride concentrations, and high serum CRP level. This narrower difference between sodium and chloride concentrations may be associated with the presence of metabolic acidosis [35]. Our data suggested that poor nutritional status, metabolic acidosis, and inflammation were also risk factors for anemia.…”
Section: Plos Onementioning
confidence: 53%
“…Multiple regression analysis revealed that the progression of G category was a significant risk factor for anemia; other risk factors included female sex, low serum albumin level, narrower difference between sodium and chloride concentrations, and high serum CRP level. This narrower difference between sodium and chloride concentrations may be associated with the presence of metabolic acidosis [35]. Our data suggested that poor nutritional status, metabolic acidosis, and inflammation were also risk factors for anemia.…”
Section: Plos Onementioning
confidence: 53%
“…Data without related eGFR values were extracted for 1 week before or 1 week after an eGFR value was recorded [23]. The difference between serum sodium and chloride concentrations was determined as serum Na-serum Cl (mEq/L) [30]. Serum corrected calcium level was calculated using Payne's correction formula: measured serum calcium level + (4 -serum albumin level) (mg/dl) [31].…”
Section: Data Collectionmentioning
confidence: 99%
“…The J-CKD-DB study enables large-scale analysis directly linked to the electronic medical record by using the SS-MIX2 standard, and is an important precursor to large-scale analyses of complications in Japanese patients with CKD. Previous studies reported the prevalences of electrolyte abnormalities in patients with CKD who were treated by nephrologists [14,17,30]. Here, we examined the sampling rate of electrolytes in an electronic health record study cohort, which was not limited to patients receiving treatment from nephrologists.…”
Section: G3amentioning
confidence: 99%
See 1 more Smart Citation
“…Причинно-следственные связи между приемом диуретиков и ХБП требуют осторожной интерпретации. С одной стороны, диуретики могут оказывать негативный эффект на тубулоинтерстиций почек, вызывая метаболический ацидоз [14], активацию ренин-ангиотензиновой системы [15] или гипокалиемию [16]. Причиной снижения СКФ могут быть более частые эпизоды снижения артериального давления (АД) и преренального острого почечного повреждения на фоне одновременного применения диуретиков с другими гипотензивными препаратами, особенно блокаторами медленных кальциевых каналов [17].…”
Section: обсуждение основного результата исследованияunclassified